Perceived images of Kuala Lumur from the perspective of international tourists - Syed Jaafar, Syed Muhammad Rafy (2017)
Most existing literature on destination image studies focus on measuring tourist perceived image using the perspective of ‘before and after’ visitation. However, a question arises as to how these efforts represent an accurate image of the tourist experience during their visit in a particular destination. It is crucial since it gives a perspective of the actual image of a destination. Therefore, this study aims to capture the overall image perceived by tourist before, during and after visitation at an urban tourism destination. Kuala Lumpur was selected as a case study due to its aggressive attempt on becoming a world class business destination, where promoting an accurate destination image is crucial for city positioning and only achievable if the image is portrayed from the demand side. Within this context, the technological innovation and trends, for instance, increase the possibility of capturing actual image that is perceived by tourist during visitation. The Volunteer Employed Photographer (VEP) technique was used due to its advantage in capturing affective elements of a destination and the photographs indirectly represent real tourist emotions towards a destination. Capturing affective elements is vital as it contributes towards the overall image of a destination. A total of 384 international tourists participated in two stages of the survey for this study, using the questionnaire and VEP techniques and conducted within the Kuala Lumpur Business District (KLBD). Descriptive and inferential analyses were used to obtain mean, variance and standard deviation from the collected data. One-Way ANOVA, t-test and correlation analyses were further used to investigate significant differences across variables. The findings indicate that international tourists perceived KLBD differently before and during visitation. Before visitation, cognitive and affective images of tourists differed according to their demography, information sources, and travel characteristic. Elements of expenditure and food were dominant in the cognitive images while culture, expenditure, and food were dominant in the affective images perceived by tourists before visiting city. Supplemental photo analysis showed that image during visitation is constantly changing as the tourists experience different locations based on their movement and preferences. Images of places, crowds of people, food and expenditure activities dominated the overall photo content. However, these perceived images are influenced and dictated by tourist’s age, country of origin, and travel companion. The overall evaluation of the actual images show that KLBD offers passive activities with physical attributes triggering positive and negative attitudes with active emotions. Acknowledging the image changes perceived by tourist on each stage helps in understanding the image influencing tourist tendency to revisit the destination. Acquiring image perceived by tourist during visitation is critical to assist tourism agencies and authorities in promoting accurate image in order to promote higher tourism satisfaction since different tourists have different preferences.